2015
DOI: 10.1016/j.ijpharm.2015.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible microemulsions of a model NSAID for skin delivery: A decisive role of surfactants in skin penetration/irritation profiles and pharmacokinetic performance

Abstract: To elaborate the decisive role of surfactants in promotion of aceclofenac' skin absorption, potentially avoiding irritation, we developed non-ionic microemulsions varying natural or synthetic surfactants: sucrose esters (laurate or myristate) vs. polysorbate 80. A comprehensive physicochemical characterization indicated no significant influence of the solubilized nonsteroidal anti-inflammatory drug on the bicontinuous structure of blank formulations. To evaluate skin tolerability of isopropyl alcohol, a sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 46 publications
4
16
0
Order By: Relevance
“…However, in the case of ME1 a stronger interaction between water and surfactant at the interface can be hypothesized, this causes the freezing point to move to very low temperatures (-60°C), although with minor intensity, due to a lower water content than ME2. This water behaviour has been already found for W/O MEs in previous works [31,40]. By comparing the curves of the single components (data not shown), a characteristic peak for ME1 (around -40°C) attributed to olive oil can be also observed.…”
Section: Differential Scanning Calorimetry (Dsc) Measurementssupporting
confidence: 85%
See 2 more Smart Citations
“…However, in the case of ME1 a stronger interaction between water and surfactant at the interface can be hypothesized, this causes the freezing point to move to very low temperatures (-60°C), although with minor intensity, due to a lower water content than ME2. This water behaviour has been already found for W/O MEs in previous works [31,40]. By comparing the curves of the single components (data not shown), a characteristic peak for ME1 (around -40°C) attributed to olive oil can be also observed.…”
Section: Differential Scanning Calorimetry (Dsc) Measurementssupporting
confidence: 85%
“…Overview images showed distinct ME droplets with spherical shape and a good size homogeneity (Supplementary Figure S3b,c) which can be clearly attributed to the W/O systems herein developed. In this case, we did not report images of drug loaded formulations since it has been already demonstrated that the addition of the drug did not significantly influence the vehicles nanostructure [31]. This assumption is also in accordance to most of experimental parameters above reported.…”
Section: Atomic Force Microscope (Afm) Studiessupporting
confidence: 79%
See 1 more Smart Citation
“…Additionally, w/o µEs are particularly interesting for oral protein delivery due to their increased oral bioavailability through the gastrointestinal tract and their protection capacity [ 144 ]. A large number of drugs, such as antibiotics [ 141 , 142 , 143 , 144 , 145 , 146 ], antifungals [ 147 , 148 , 149 ], anti-inflammatory [ 150 , 151 , 152 , 153 , 154 ] and immunosuppressive [ 155 ] molecules have been used in μEs systems.…”
Section: Achievements and Challengesmentioning
confidence: 99%
“…There is less concern over colloidal nanosystems such as emulsions and lipid-based materials because these are likely to be biodegradable on application to the skin, although the molecular products will still be assessed in the usual way for irritancy and cytotoxicity. For example, Todosijević et al [193] used changes in erythema index, skin hydration and TEWL to assess the skin…”
Section: Safety and Adverse Effectsmentioning
confidence: 99%